THE IMPACT OF GOVERNMENT REGULATION ON THE ECONOMIC EFFICIENCY OF THE TELECOMMUNICATIONS INDUSTRY - Mustam (Adisam Publisher, 2024)
Government policy in the telecommunications industry is aimed at ensuring economic efficiency by regulating tariffs, spectrum management, and encouraging fair competition. These regulations are important because they prevent market domination by foreign companies, such as those regulated in the rules regarding share ownership by foreign investors with certain limits. The study conducted in this research used the literature research method. The results show that first, well-designed regulations can increase economic efficiency by keeping tariffs affordable, optimising spectrum usage, and encouraging healthy competition among companies. Second, overly strict or bureaucratic regulations can slow innovation and infrastructure investment, which in turn can hinder the growth and efficiency of the telecommunications industry. Third, excessive regulation can have negative impacts, such as lengthening the licensing process and reducing companies' incentives to invest in research and development. On the other hand, the absence of adequate regulation can trigger anti-competitive practices and market abuse, which also adversely affect economic efficiency. Thus, it is important to find the right balance in regulation such as being strict enough to maintain fairness and transparency, but also flexible enough to allow for innovation and quick responses to technological change.